2010
DOI: 10.1007/s11302-010-9203-x
|View full text |Cite|
|
Sign up to set email alerts
|

Ebselen is a potent non-competitive inhibitor of extracellular nucleoside diphosphokinase

Abstract: Nucleoside di-and triphosphates and adenosine regulate several components of the mucocilairy clearance process (MCC) that protects the lung against infections, via activation of epithelial purinergic receptors. However, assessing the contribution of individual nucleotides to MCC functions remains difficult due to the complexity of the mechanisms of nucleotide release and metabolism. Enzymatic activities involved in the metabolism of extracellular nucleotides include ecto-ATPases and secreted nucleoside diphosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
2
5
0
Order By: Relevance
“…3A) showed that ebselen inhibited DOXol formation by a noncompetitive mechanism (K i = 5.586 6 0.254 mM). The same inhibition behavior has previously been observed for other enzymes treated with ebselen (Schewe et al, 1994;Semianrio-Vidal et al, 2010). Moreover, the inhibition was irreversible because ultrafiltration or long-term dialysis of ebselen-treated heart cytosolic fractions failed to restore anthracycline reductase activity (activity recovery was less than 5%).…”
Section: Resultssupporting
confidence: 78%
“…3A) showed that ebselen inhibited DOXol formation by a noncompetitive mechanism (K i = 5.586 6 0.254 mM). The same inhibition behavior has previously been observed for other enzymes treated with ebselen (Schewe et al, 1994;Semianrio-Vidal et al, 2010). Moreover, the inhibition was irreversible because ultrafiltration or long-term dialysis of ebselen-treated heart cytosolic fractions failed to restore anthracycline reductase activity (activity recovery was less than 5%).…”
Section: Resultssupporting
confidence: 78%
“…The data are supportive of a complex link between the activities of AMPK and NDPK-A which co-localize 23 (see below). This is compatible with our early data on chloride as a signal to phosphohistidine generation and perhaps there exists a latent functional inter-regulation between NDPK, that is part of an epithelial, chloride-sensitive, membranedelimited phosphorylation system working with membranebound AMPK 76 in association with CFTR.…”
Section: Regulation Of Cftr Activity By the 5′-amp-acti-vated Proteinsupporting
confidence: 91%
“…There has been considerable interest in applications of selenolate compounds because of their broad therapeutic spectrum and low toxicity. The organoselenium compound ebselen [2-phenyl-1,2-benzisoselenazol-3(2H)-one] an anti-inflammatory and general antioxidant, is also a potent inhibitor of extracellular nucleoside diphosphokinase [ 26 ]. Furthermore, Achillion Pharmaceuticals (New Haven, CT, USA) has recently developed a selenophene inhibitor of bacterial topoisomerases that shows promise as an antibiotic [ 27 ].…”
Section: Discussionmentioning
confidence: 99%